2015
DOI: 10.1021/acs.jafc.5b01238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of d-Pinitol on Insulin Resistance through the PI3K/Akt Signaling Pathway in Type 2 Diabetes Mellitus Rats

Abstract: D-pinitol, a compound isolated from Pinaceae and Leguminosae plants, has been reported to possess insulin-like properties. Although the hypoglycemic activity of D-pinitol was recognized in recent years, the molecular mechanism of D-pinitol in the treatment of diabetes mellitus remains unclear. In this investigation, a model of type 2 diabetes mellitus (T2DM) with insulin resistance was established by feeding a high-fat diet (HFD) and injecting streptozocin (STZ) to Sprague-Dawley (SD) rats, targeting the explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
97
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 25 publications
2
97
2
2
Order By: Relevance
“…Previous studies have reported that a diet supplemented with L. casei strain CCFM419 increases glucose tolerance in HFD/STZ‐induced T2DM rats, L. rhamnosus GG improves glucose tolerance in STZ‐induced diabetic rats and that the impaired glucose tolerance in HFD‐fed mice is alleviated by L. fermentum strain MTCC 5689 administration, consistent with our studies. PI3K/Akt signalling pathway plays a crucial role in insulin action to regulate glucose and lipid metabolism and a long‐term HFD blunts this pathway . L. casei CCFM419 was reported to improve insulin resistance through the PI3K/Akt pathway with upregulation of PI3K and GS and downregulation of GSK‐3β mRNA expression .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that a diet supplemented with L. casei strain CCFM419 increases glucose tolerance in HFD/STZ‐induced T2DM rats, L. rhamnosus GG improves glucose tolerance in STZ‐induced diabetic rats and that the impaired glucose tolerance in HFD‐fed mice is alleviated by L. fermentum strain MTCC 5689 administration, consistent with our studies. PI3K/Akt signalling pathway plays a crucial role in insulin action to regulate glucose and lipid metabolism and a long‐term HFD blunts this pathway . L. casei CCFM419 was reported to improve insulin resistance through the PI3K/Akt pathway with upregulation of PI3K and GS and downregulation of GSK‐3β mRNA expression .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be used as a supplement to treat type II diabetes mellitus (Bates, Jones, & Bailey, 2000). Gao et al (2015) reported that d-pinitol played an important role in regulating insulin-mediated glucose uptake for the rats having type II diabetes mellitus. It can also be used to treat AIDS by decreasing the number of HIV in human body (Mills, Cooper, Seely, & Kanfer, 2005).…”
mentioning
confidence: 99%
“…Pinitol, also called D-pinitol, is a compound with multifunctional properties, among them, anti-inflammatory, cardioprotective, and anti-hyperlipidemicactions. Furthermore, pinitol is known to have properties similar to those of insulin [5961]. …”
Section: Discussionmentioning
confidence: 99%